Compulsory methadone maintenance treatment of severe cases of drug addiction in a residential setting in Tehran, Iran (2): Outcome evaluation in two and six-month follow-up - Afarin Rahimi-Movaghar; Golara Khastoo; Emran Razzaghi; Mohammad Bagher Saberi-Zafarghandi; Ali Reza Noroozi; Reza Jar-Siah (Payesh, 2011)
Objective(s): An urgent project for arresting and mandatory treatment of high risk drug addicts started in May 2007 in Tehran. After triage, those with more severe patterns were sent to a residential center for compulsory methadone maintenance treatment. This paper presents the outcomes in two and six-month follow-up. The results of process evaluation of interventions were presented in the first paper.Methods: A total of 500 addicts that have been arrested within 11 days were followed. Seventy nine were sent to the residential center. Follow-up of these arrestees within the center, and two and six months after discharge were carried out through individual interviews, focus group discussions, morphine test in urine, and review of the records.Results: From the 79 individuals entering the residential center, 51 were discharged after two months. Fifteen (29.4%) was in treatment in two month follow-up and 7 (13.7% from 51) had negative morphine test. In six month follow-up, retention rate was 23.5% (11 of 51) and morphine test was negative in 6 (11.8% from 51).Conclusion: Because of the criminal approach to addiction in the country and provision of various punishments in anti-drug law, this was the first scientific approach to mandatory treatment. Although the positive outcomes are less than the results of other compulsory treatments like Drug Court Treatment, but with improvements in the provided services, utilization of a variety of approaches, and promoting aftercare services, the outcomes can improve, considerably.